Sleep SAAF responsive parenting intervention improves mothers' feeding practices: a randomized controlled trial among African American mother-infant dyads - Erika Hernandez; Justin A. Lavner; Amy M. Moore; Brian K. Stansfield; Steven R. H. Beach; Jessica J. Smith; Jennifer S. Savage (BMC, 2022)
Abstract Background/Objective Parents shape children's early experiences with food, influencing what is served, children's food choices, and how much children eat. Responsive parenting (RP) interventions such as INSIGHT have improved maternal infant feeding practices, but have only been tested among predominantly White families. This secondary analysis of data from the Sleep SAAF (Strong African American Families) RCT tests the effects of an RP intervention designed to prevent rapid infant weight gain on African American mothers' infant feeding practices. Methods Primiparous African American mother-infant dyads (n = 194) were randomized to an RP or safety control intervention delivered by community research associates at infant age 3 and 8 weeks. At 16 weeks, mothers completed the Babies Need Feeding questionnaire, the Infant Feeding Styles Questionnaire, and the Babies Need Soothing questionnaire. Logistic regression and general linear models examined the effect of study group on infant feeding practices. Moderation analyses explored whether effects varied by feeding mode (any breast milk versus exclusive formula), maternal age (≥ 20 years versus < 20 years), and maternal pre-pregnancy BMI (with obesity versus not). Results RP mothers reported more responsive feeding (p = 0.005, partial η2 = 0.02), lower likelihood of using beverages other than breast milk/formula to soothe their infant (p = 0.01, OR = 0.42, 95% CI [0.2-0.8]), and less pressure with cereal than control mothers (p = 0.09, partial η2 = 0.02). RP mothers also reported less pressure to finish/soothe than controls (p = 0.007, partial η2 = 0.04); feeding mode (B = 0.74, p = 0.003) and maternal age (B = 0.53, p = 0.04) moderated this effect. There were no significant group differences in bottle-feeding practices (e.g., adding cereal to bottle, using an appropriate nipple/bottle size), or in context-based or emotion-based food to soothe. Conclusions Responsive parenting education influenced some feeding practices of African American mothers. Mothers reported using less pressure, a control-based feeding practice, and more responsive feeding than controls. Trial registration Sleep SAAF: A Strong African American Families Study. www.clinicaltrials.gov NCT03505203. Registered 3 April 2018.